The Influence of Sales Growth and Profit Growth on Financial Distress with Asset Growth as a Moderating Variable - Nurul Istiqomah; Irma Indira (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2025)
The aim of the research is to see whether sales growth and profit growth can influence financial distress with asset growth as a moderate variable. The research object was carried out at sub-companies with a total of 45 annual financial reports. The tool used for data analysis is SmartPLS 3.0. The results explain that sales growth has a significant negative effect on financial distress. Profit growth does not have a significant effect on financial distress. Asset growth does not have a significant effect on financial distress. Asset growth cannot moderate the influence of sales growth on financial distress. Asset growth cannot moderate the influence of profit growth on financial distress in the retail sub-sector on the BEI in 2021-2023.